Dosis de aceite rojo de palma en la dieta en el rendimiento de pollos Cobb 500. Zúngarococha. Loreto - Sánchez Ramírez, Manuel Aldair (2025)
The purpose of this study was to evaluate the effect of different doses of red palm oil incorporated into the diet on the productive performance of Cobb 500 chickens raised in tropical conditions in Zúngarococha, Loreto region. This research arises in response to the need to improve feed efficiency in poultry systems through the use of accessible natural additives with high energy value. The general objective was to determine the impact of five levels of inclusion of red palm oil (0, 5, 10, 15 and 20 g/kg of feed) on productive variables such as final live weight, feed intake, weight gain, feed conversion and feed efficiency. To do this, a completely randomized design (DCA) was used with 100 birds equally distributed among the treatments, applying statistical analysis by ANOVA and Tukey's test in the RStudio software. The results showed that the inclusion of 15 g/kg of red oil (T3) generated significant improvements in all the variables evaluated, achieving greater weight gain (1735 g), lower feed conversion (2.08) and higher feed efficiency (48.17%), compared to the control group. It is concluded that red palm oil, in intermediate doses, represents an efficient and sustainable alternative to increase poultry productivity. Its use in commercial broiler diets is recommended and its future evaluation in aspects of gut health and meat quality is recommended.